1992
DOI: 10.1901/jaba.1992.25-561
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Learning Analysis of Decisions in Organizations to Escalate Investments Despite Continuing Costs or Losses

Abstract: Reinforcement process may underlie decisions frequently found in organizations to escalate investments of time, money and other resources in strategies (e.g., product development, capital investment, plant expansion) that do not result in immediate reinforces. Whereas cognitive biases have been proffered in previous explanations, the present analysis suggested that this persistence is a form of resistance to extinction arising from experiences with past investments that were variably reinforced. This explanati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
1
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(110 citation statements)
references
References 24 publications
13
95
1
1
Order By: Relevance
“…The fact that our results are consistent with experiments conducted on persistence and escalation under different conditions (see, e.g., Golz, 1992;Brecher & Hantula, 2005) 19 speaks, in our view, to the strength of the reinforcement manipulation in our experiment and rules out the need to postulate social explanations such as self-justification (Brockner, 1992). Note, however, that we are not arguing that processes such as self-justification do not occur when persistence is observed in naturally occurring environments.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The fact that our results are consistent with experiments conducted on persistence and escalation under different conditions (see, e.g., Golz, 1992;Brecher & Hantula, 2005) 19 speaks, in our view, to the strength of the reinforcement manipulation in our experiment and rules out the need to postulate social explanations such as self-justification (Brockner, 1992). Note, however, that we are not arguing that processes such as self-justification do not occur when persistence is observed in naturally occurring environments.…”
Section: Discussionsupporting
confidence: 93%
“…For example, in a field study, Deslauriers and Everett (1977) showed how, to increase bus ridership, it was more effective to offer passengers variable as opposed to continuous reinforcement (gifting tokens to roughly every one in three passengers versus every passenger receiving a token). Golz (1992) pioneered an experimental game in which groups of participants could earn or lose money by investing under continuous and variable reinforcement conditions. In the acquisition phase, the market allowed participants to be successful; in the extinction phase, it did not.…”
Section: Related Literaturementioning
confidence: 99%
“…In addition, this approach permits a priori prediction of responding, reinforcement, and punishment in situations of choice (Herrnstein, 1970(Herrnstein, , 1990. Finally, a behavioral economic framework allows integration of these clinical assessment and treatment data with the growing synthesis of behavioral and economic principles (Akerlof, 1991;Becker, 1976;Goltz, 1992;Hantula & Crowell, 1994;Hursh, 1980;Tustin, 1994) predicted by Kagel and Winkler (1972) over two decades ago.…”
Section: Discussionmentioning
confidence: 99%
“…The INVE$TMENT CHOICE$ MW (Hantula & Crowell, 1994a, 1994b) was used to investigate how changes in the patterning of investment return rates affected investment decisions during trials in which subjects made money or steadily lost money (this research replicated and extended work by Goltz, 1992, who used a similar MW task). The continued investment of resources despite steady losses has been dubbed "escalation and persistence of commitment" in the organizational psychology literature (Hantula, 1992;Staw & Ross, 1989).…”
Section: Inve$tment Choice$mentioning
confidence: 92%
“…Single decisions may be the product of an entirely different class of variables than are repeated decisions (Sitkin & Pablo, 1992). It is entirely probable that distinct levels of horizontal analysis may exist (such as a single decision, two decisions in sequence, three in sequence, and greater than three in sequence), and with them issues ofpattern and cyclicity (Goltz, 1992;Hantula & Crowell, 1994b), chaos (Barton, 1994), "strings" of gains and losses (Rachlin, 1990;Rachlin & Siegel, 1994), and temporal discounting (Ainslie, 1992;Kirby & Marakovic, 1995), which ought to be considered in a useful understanding of phenomena.…”
Section: Mundane Realismmentioning
confidence: 99%